Bradycardia, renal failure, shock, and hyperkalemia (BRASH) caused by AV nodal blocker: a case report of a patient with BRASH syndrome resistant to calcium administration - Sidhi Laksono; Ananta Siddhi Prawara (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2022)
Chronic kidney disease patients commonly present in a clinical setting with hypertension may cause or affect the disease. Carvedilol, a beta-blocker that is routinely used to treat hypertension in chronic kidney disease, was proven to be safer compared to other beta-blockers. However, it may still cause AV nodal block. AV nodal block can cause bradyarrhythmia, resulting in low cardiac output and low blood supply to multiple organs, including the kidney. This condition further impaired the kidney function in regulating potassium levels and cause hyperkalemia. Hyperkalemia, in return, can also cause bradycardia, and the vicious cycle goes on and on. Previous studies reported that calcium gluconate administration might significantly improve the patient’s condition. However, in this case, calcium gluconate failed to give significant improvement even though it reduced the potassium level. We report a 53 years old male patient on carvedilol with bradyarrhythmia, chronic kidney disease, shock, and hyperkalemia (BRASH syndrome) that failed to resolve with calcium gluconate administration.